Haemoglobin Adana in alpha thalassaemia intermedia in the Malaysian population - Lee, Tze Yan (2017)
Alpha thalassaemia is an autosomal blood disorder due to a quantitative reduction or total absence of alpha globin chain synthesis caused by alpha globin gene mutations. Alpha thalassaemia intermedia or more commonly known as HbH disease is a form of thalassaemia with intermediate severity. A total of 3 out of 4 alpha globin genes are nonfunctional. There are two main types of HbH disease, the deletional and non-deletional HbH disease. There are limited studies in Malaysia on alpha thalassaemia intermedia particularly the severe form of non-deletional alpha thalassaemia like Hb Adana. Hence, it is imperative to identify alpha thalassaemia intermedia with its spectrum, origin of mutations and genotype-phenotype correlation. We hypothesized that Hb Adana is an important severe alpha thalassaemia and its molecular basis needs to be further elucidated for better understanding. Genotype-phenotype correlation was done on the 320 alpha thalassaemia intermedia cases collected. Three main groups from the pool of alpha thalassaemia cases were categorized into deletional HbH, non-deletional HbH, non-deletional alpha thalassaemia. The most common alpha thalassaemia genotypes found in this study is the -α3.7/--SEA which forms more than 50% (55.3%) of the cases. The non deletional HbH cases have a lower Hb, RBC, MCHC and HbA2 mean value than deletional HbH. However, the RDW, MCV and MCH of the non-deletional HbH cases are higher than the deletional HbH. A rapid detection method to screen α-thalassaemia variants was also evaluated by using the new technology of digital droplet PCR (ddPCR). The design of this assay encompasses the detection of triplications, common and rare deletional alpha thalassaemia by ultilising this new technology. This quantitative method was found to be able to measure and determine the copy number changes therefore could simultaneously detect deletions, duplications and triplications of the alpha globin gene cluster. Hence, ddPCR is an alternative method for rapid detection of alpha thalassaemia variants in Malaysia. The ddPCR was also able to detect Hb Adana (Cd59) which is a SNP mutation. Both the wild type and heterozygous Hb Adana mutation was successfully characterised using the ddPCR method. All Hb Adana cases were then subjected to direct sequencing and PCR RFLP to determine the position of Cd59 mutation on the alpha globin gene. All the 36 cases of Hb Adana have the Cd59 position on α2 globin gene. Majority of the Hb Adana samples found were of the Malay ethnicity in the alpha thalassaemia intermedia pool. Further investigations on the haplotype patterns revealed that most of the Hb Adana cases belongs to the Haplotype I pattern (53.8%) in Malaysia. This suggests that the Hb Adana pool in Malaysia has a distinctive pattern and there is a high possibility that they might well be from the same genetic pool and quite similar to the one from Indonesia. In conclusion, Hb Adana with mutation at α2 globin gene and its distinctive haplotype pattern is found predominantly in the Malay population in Malaysia.